The Impact Of Market Orientation on The Innovative performance Of Small and Medium Enterprises (A field study in Lattakia Governorate) - عيسى يارا (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the study was to shed light on each of the market orientation with its dimensions: customer orientation, competition orientation, internal coordination, and to shed light on innovative performance, and to show the impact of market orientation and the impact of each. After we realized the dimensions of innovative performance of small and medium enterprises, we relied on the descriptive analytical approach. In the theoretical section, we sought to address the concept of market orientation and its dimensions (customer orientation, competition orientation, internal planning), and the concept of innovative performance and its importance were addressed. In the practical section, a questionnaire was designed consisting of 25 statements that included a set of statements related to the research variables, and appropriate statistics were used based on the (SPSS23) program in analyzing the data and testing the hypotheses. The study showed the existence of a continuous, significant, medium impact of market orientation on the innovative performance of small and medium enterprises in the study area.